Identifying the Growth Centers Connectivity Based on Road Network and Market Accessibility in the North-West Part of Bangladesh (Journal of Bangladesh Institute of Planners, 2017)
Different socio-economic theories suggest that Growth Center is a major connection between urban and rural areas and an effective rural development strategy. The purpose of the study is to reveal the connectivity of neighboring growth centers supported by road network and market accessibility of rural areas of the south-west part of Bangladesh. This analysis will help to realize the connectivity of growth centers in rural development through rural-urban connectivity and grow attention in growth center development. Among the 539 Growth Centers of this region, 2 Growth Centers have been selected randomly from the two different districts which are Machmail Hat (Baghmara unionRajshahi district-Rajshahi division) and Kachinia Hat (Khansama union-Dinajpur districtRangpur division). The data has been collected through observation, focus group discussion, questionnaire survey, and also secondary sources like LGED, BBS, local NGOs, Union Parishad, research papers, etc. The analysis shows a good connectivity of the growth centers with the nearer growth centers though mainly with local roads and shows a good marketing relationship where the intermediate persons play a major role.JBIP, Vol. 10, 2017 (Printed in December 2019), pp. 105-115